Epidemiological Correlates Of Unmet Need For Contraception In Urban Slum Population - Supriya Satish Patil*, MP Durgawale and SR Patil (Al Ameen Medical College, 2010)
This study was undertaken to find out magnitude and identifying the different variables, which are associated with unmet need for contraception among married women in the age group of 15-44 yrs in an urban slum of Karad, Maharashtra. A cross-sectional community based study was carried out among married women aged 15-44 yrs. Personal interview method with house-to-house visit was adopted as the study method. In this study unmet need for contraception was found in 59 (45.1%) women, need for spacing in 25 (19.1%) and need for limiting birth in 34 (26%) women. About 81.3% of women in the unmet group belong to the age 15-29 yrs. There was significant association between prevalence of unmet need and age, number of living children, education. There was no significant association found between occupation, religion and unmet need for contraception. The present study revealed that lack of information about contraceptive method and its sources (57.6%) were the common reasons for non-acceptance of contraception. It can be concluded that health education campaigns are necessary to increase awareness and counseling of eligible couples on importance of small family norm is essential.